Two new species of Spinicaudata (Crustacea: Branchiopoda) in south India with a key to Leptestheriella and Eocyzicus - Simhachalam, Gullipalli; Timms, Brian V. (Zootaxa, 2012)
Five species of Leptestheriella (Daday 1923) have been described from India, but variability in many characters suggestsonly two are valid: L. nobilis (Sars 1900) and L. sarsi Daday 1923. We add Leptestheriella simhadrii sp. nov. which isdistinct in its carapace and growth line ornamentation and in females of having the endopodital palp on the fifth endite ofthe third thoracopod slightly longer than the sixth endite. A key is provided to distinguish the three species. Eight de-scribed and one unconfirmed species of Eocyzicus (Daday 1915) have been reported from India. We add Eocyzicus pal-palis sp. nov. from south India and present a key to local species. Eocyzicus palpalis sp. nov. is distinct by reason of itsornamentation of the carapace, the presence of a palp on the fourth endite of the third thoracopod and the fifth endite of the sixth and seventh thoracopods which bears a palp and plumose setae in males.